Welcome to Westonci.ca, the Q&A platform where your questions are met with detailed answers from experienced experts. Discover comprehensive answers to your questions from knowledgeable professionals on our user-friendly platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
i know this wont help but y=mx+c or +b will need to be used so y will equal to 3x+5 so the equasion is y=3x+5
sorry, thats all i can do
sorry, thats all i can do
y - y₁ = m(x - x₁)
y - 5 = 3(x - (-2))
y - 5 = 3(x + 2)
y - 5 = 3(x) + 3(2)
y - 5 = 3x + 6
+ 5 + 5
y = 3x + 11
y - 5 = 3(x - (-2))
y - 5 = 3(x + 2)
y - 5 = 3(x) + 3(2)
y - 5 = 3x + 6
+ 5 + 5
y = 3x + 11
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.